2013
DOI: 10.1111/mice.12039
|View full text |Cite
|
Sign up to set email alerts
|

Defect Detection in Reinforced Concrete Using Random Neural Architectures

Abstract: Detecting defects within reinforced concrete is vital to the safety and durability of our built infrastructure upon which we heavily rely. In this work a noninvasive technique, ElectroMagnetic Anomaly Detection (EMAD), is used which provides information into the electromagnetic properties of the reinforcing steel and for which data analysis is currently performed visually: an undesirable process. This article investigates the first use of two neural network approaches to automate the analysis of this data: Ech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 47 publications
(52 reference statements)
0
50
0
Order By: Relevance
“…A PNN is a feedforward neural network [20,51] with four layers: an input layer, a pattern layer, a summation layer, and an output layer [49], shown in Fig. 1 for the classification of HC, SWEDDs, and PD subjects using the PPMI database.…”
Section: Probabilistic Neural Networkmentioning
confidence: 99%
“…A PNN is a feedforward neural network [20,51] with four layers: an input layer, a pattern layer, a summation layer, and an output layer [49], shown in Fig. 1 for the classification of HC, SWEDDs, and PD subjects using the PPMI database.…”
Section: Probabilistic Neural Networkmentioning
confidence: 99%
“…More recently, they have been used in domains such as electric load forecasting [15], sports activity classification [16] and shape recognition [17]. ESNs have also previously been used in a structural health monitoring context: for fault diagnosis in a water network [18] and defect detection in reinforced concrete [19]. In all of these studies, ESNs were found to equal, or outperform, a number of other state-of-theart techniques.…”
Section: B Echo State Networkmentioning
confidence: 99%
“…The ability of ESNs to exhibit a short term memory means that most applications have involved either time-series data -in areas such as audio classification [16] and recognition of forehands in tennis [17] -or spatially varying data, such as raw magnetic flux leakage data [18], [19], and microscopic cellular image segmentation [20]. The use of ESNs on static data is not new but is quite rare and, of the few approaches that do exist, most involve a procedure for allowing the state of the reservoir to settle as each static input pattern is repeatedly presented: a process characterised as clamping [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%